Clonal evolution of acute myeloid leukemia from diagnosis to relapse - Vosberg, Sebastian (Genes Chromosomes Cancer, 2019)
Based on the individual genetic profile, acute myeloid leukemia (AML) patients are classified into clinically meaningful molecular subtypes. However, the mutational profile within these groups is highly heterogeneous and multiple AML subclones may exist in a single patient in parallel. Distinct alterations of single cells may be key factors in providing the fitness to survive in this highly competitive environment. Although the majority of AML patients initially respond to induction chemotherapy and achieve a complete remission, most patients will eventually relapse. These points toward an evolutionary process transforming treatment‐sensitive cells into treatment‐resistant cells. As described by Charles Darwin, evolution by natural selection is the selection of individuals that are optimally adapted to their environment, based on the random acquisition of heritable changes. By changing their mutational profile, AML cell populations are able to adapt to the new environment defined by chemotherapy treatment, ultimately leading to cell survival and regrowth. In this review, we will summarize the current knowledge about clonal evolution in AML, describe different models of clonal evolution, and provide the methodological background that allows the detection of clonal evolution in individual AML patients. During the last years, numerous studies have focused on delineating the molecular patterns that are associated with AML relapse, each focusing on a particular genetic subgroup of AML. Finally, we will review the results of these studies in the light of Darwinian evolution and discuss open questions regarding the molecular background of relapse development.